Exploration Of Horse Leather Material As Raw Materials In Making Footwear - Asep Sufyan (Balong International Journal of Design, 2019)
Horse leather material has not been popular among consumers, of course, being a separate obstacle in the sale of products that use horse leather material. Horse leather is a material that is rarely used, if this horse leather material is used appropriately, this can be a selling point for that product. In addition, if you use an attractive selling strategy, this can attract the attention of consumers and increase sales figures. Treatment of horse skin material is not as difficult as imagined, it is enough to use a toothbrush and shampoo to clean it if it is dirty and brushed in the direction of the horse's hair so as not to damage its texture.The process of designing starts from seeing the trends that are taking place in the community, of course, trends related to footwear, by looking at the trends that are taking place in the community we can get a target market from which people will be the target in the design process footwear. The design is done by going through several stages such as sketches, digital rendering by inserting material into the rendering to make it easier to imagine, and also making alternative colors.